A Comparison of Intranasal Dexmedetomidine, Esketamine or a Dexmedetomidine-Esketamine Combination for Induction of Anaesthesia in Children: A Randomized Controlled Double-Blind Trial - Lu, Xinlei; Tang, Ling; Lan, Haiyan; Li, Chunli; Lin, Han (Frontiers in Pharmacology, 2022)
Objective: To compare the efficacy of dexmedetomidine, esketamine or combined intranasal administration on the induction of inhalation anaesthesia in children. Methods: Ninety children aged 1–6 years were randomly allocated into three equal groups to be premedicated with either intranasal dexmedetomidine 2 μg/kg (Group D), esketamine 1 mg/kg (Group S), or dexmedetomidine 1 μg/kg combined with esketamine 0.5 mg/kg (Group DS). The primary endpoint was the Induction Compliance Checklist (ICC) Scale. Secondary outcomes included the sedation success rate; the modified Yale Preoperative Anxiety Scale score; the time of reaching up to two points on the University of Michigan Sedation Scale (UMSS); Parental Separation Anxiety Scale; anaesthesiologist satisfaction with induction based on the visual analogue scale; emergence agitation scale score; and adverse effects. Results: The children in the DS group showed a high degree of cooperation with inhalation anaesthesia induction, and their ICC score was significantly lower than that of the D and S groups (p = 0.001), but there was no difference between the D and S groups. The success rate of sedation was higher in Group DS (90%) than in Group D (70%) and Group S (53.3%) (p = 0.007). Anaesthesiologist satisfaction with induction was significantly higher in Group DS than in Groups D and S (p = 0.001). The incidence of emergence agitation and the Paediatric Anaesthesia Emergence Delirium (PAED) score in the DS group were lower than those in the D and S groups. Conclusions: Preoperative intranasal administration of dexmedetomidine combined with esketamine can significantly improve the cooperation of children with inhalation anaesthesia masks. It is a sedation method that has a high success rate and reduces the incidence and degree of emergence agitation.